Enhanced 355 nm lasers obtained from BBO and KDP by sum frequency mixing - Kundwal, Moses Elisha (Springer, 2015)
A key challenge to researchers in optics and photonics is the lack of suitable broadband lasing materials for the ultraviolet (UV) domain. Hence, the use of nonlinear optics for generation of harmonics for the UV domain, from either infrared (IR) or visible (Vis) lasers. In this work, we made use of nonlinear optical conversion to develop a compact 355 nm pulsed UV laser from a passive Q-switched pulsed infrared laser (1,064 nm). Two nonlinear crystals, barium borate (BBO) and potassium dihydrogen phosphate (KDP), are, in turn, used to generate the third harmonic of the IR laser by frequency mixing, after initial frequency doubling through a potassium titanyl phosphate (KTP) crystal. We make the laser user friendly by constructing crystal holders for the nonlinear crystals so that it becomes easier to angle tune the crystals for optimum generation of the third harmonic. The UV laser is stable and has output pulse energy up to 148 and 110 mJ, with conversion ratio from IR to UV of about 0.29 and 0.21 for BBO and KDP, respectively.